JANGKAUAN PELAYANAN SMP DI KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Gusti Rahayu 1; ahyu Ahyuni (JURNAL BUANA, 2022)
This research was conducted in Pulau Punjung district with aim of (1) knowing the reach of SMP services using the Network Analyst and Buffering methods (2) knowing which methods are more effective in determining coverage area of SMP services. This typeof reserch is a quantitative descriptive study with secondary data used. The result showed that class VII SMPN Unggul 19 students were still outside the zning. Meanwhile, class VII SMPN 6 all students are already in the zoning area. Buffering resuls at SMPN Unggul showed as many as 87students were still out of reach, Buffering at SMPN 6 out of 67 student only 8 were out of reach. The result of Network Analyst at SMPN Unggul are the same Buffering, while at SMPN 6 it shows that there are 18 student who area outside the the coverage area. In calculating the covarage of SMP services to students, the Buffering method is effective than Network Analyst because the Buffering method can cover areas.